Variación estacional de la abundancia poblacional del Calancate Común (Aratinga acuticaudata) en la Reserva Chancaní, Córdoba, Argentina - Fernandez, Esteban (1997)
We recorded the annual variation in abundance of Blue-crowned Conures (Aratinga acuticaudata) at the Chancaní Reserve, Córdoba, Argentina. This parrot was more frequently recorded during the breeding season (August, October and December) than in the non breeding season (March and May), possibly because of movements to more suitable feeding areas. The Chancani Reserve, a mature Chaco woodland, could be a source habitat that keeps populations stable at the regional level, as it provides suitable nest cavities, scarce in the surrounding agropastoral landscapeso.